A review on data transformation approaches for data migration processes from relational database to NoSQL database - Zaidi, Norwini; Ishak, Iskandar; Sidi, Fatimah; Affendey, Lilly Suriani (International Journal of Engineering and Technology, 2018)
In recent years, data migration has become an important exercise in data management due to the demand of scalable database management systems. Data transformation is an important part of data migration and researchers have put a lot of effort to produce better data transformation approaches. Based on the literatures, there are multiple ways of conducting data transformation between relation databases to NoSQL databases. However, among the issues in data transformation between the two databases are slow processing time and no definitive guideline for database administrator to guide them to conduct the transformation. This paper highlights the data transformation approaches that have been proposed by researchers in recent years as well as its strengths and limitations.